The Germans in India : Elite European migrants in the British Empire - Panayi, Panikos (Book collections on Project MUSE., 2017)
Based on years of research in libraries and archives in England, Germany, India and Switzerland, this book offers a new interpretation of global migration from the early nineteenth until the early twentieth century. Rather than focusing upon the mass transatlantic migration or the movement of Britons towards British colonies, it examines the elite German migrants who progressed to India, especially missionaries, scholars and scientists, businessmen and travellers. The story told here questions, for the first time, the concept of Europeans in India. Previous scholarship has ignored any national variations in the presence of white people in India, viewing them either as part of a ruling elite or, more recently, white subalterns. The German elites undermine these conceptions. They developed into distinct groups before 1914, especially in the missionary compound, but faced marginalisation and expulsion during the First World War.